Application of Green Marketing in the Use of Coffee Waste as A Business Creative Industry Based on Social Enterprise - Benedicta Evienia Prabawanti (Jurnal Manajemen dan Organisasi, 2020)
Coffee pulp waste is one of the most significant industrial wastes today because, in the last three years, the coffee business has increased in Indonesia, especially in urban areas. Coffee pulp waste has economic value if it can use it. This study is conducted to (1) describe the interest of coffee shops in South Jakarta to provide coffee pulp waste as cosmetic raw materials, (2) to apply green marketing as a social business strategy to develop creative industries. This research is a qualitative descriptive study with a case study approach. To discover coffee shop owners' interests to utilize coffee grounds waste, data collection through interviews with 30 coffee shop owners in South Jakarta, and observation. Determine the strategy of implementing green marketing in coffee shops through the utilization of coffee grounds waste produced. The results showed that coffee shops in South Jakarta produced 1-5 kg ​​of coffee waste per day. All owners have not utilized the coffee grounds waste. The interview results showed the coffee shop owner's desire to provide coffee pulp waste produced for use as raw material for making cosmetics. Utilizing this coffee pulp waste can lead to new businesses that can be developed as creative industries. The new company is a social business that impacts solving social problems, namely creating new jobs in environmentally friendly cosmetics made from coffee grounds waste.